Classical time-varying FAVAR models - estimation, forecasting and structural analysis - Sandra Eickmeier; Wolfgang Lemke; Massimiliano Marcellino (Deutsche Bundesbank, 2011)
We propose a classical approach to estimate factor-augmented vector autoregressive (FAVAR) models with time variation in the factor loadings, in the factor dynamics, and in the variance-covariance matrix of innovations. When the time-varying FAVAR is estimated using a large quarterly dataset of US variables from 1972 to 2007, the results indicate some changes in the factor dynamics, and more marked variation in the factors' shock volatility and their loading parameters. Forecasts from the time-varying FAVAR are more accurate than those from a constant parameter FAVAR for most variables and horizons when computed insample, for some variables in pseudo real time, mostly financial indicators. Finally, we use the time-varying FAVAR to assess how monetary transmission to the economy has changed. We find substantial time variation in the volatility of monetary policy shocks, and we observe that the reaction of GDP, the GDP deflator, inflation expectations and long-term interest rates to an equally-sized monetary policy shock has decreased since the early-1980s.
Keywords: C3; C53; E52; 330; FAVAR; time-varying parameters; monetary transmission; forecasting